Impact of BMI, osteoporosis, and disc degeneration on post-UBE lumbar stability: a finite element analysis of nonlinear synergistic effects - Ma, Jingbo; Li, Tusheng; Rozi, Rigbat; Han, Jiaheng; Jiang, Qiang; Zhang, Hanshuo; Song, Xuyan; Zhao, Guotong; Ding, Yu (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThe aim of this study is to quantify the independent and combined biomechanical effects of increased BMI, osteoporosis, and disc degeneration on lumbar segmental stability after UBE decompression, thereby informing preoperative risk stratification and guiding optimized postoperative rehabilitation protocols.MethodsA high-fidelity 3D finite-element model of the L3–S1 lumbar spine was developed using CT data of a healthy 31-year-old male volunteer in ANSYS APDL 13.0. This model was used to simulate segmental mechanics after UBE decompression. Four BMI levels (22.86, 26.12, 29.39, 32.65 kg/m2), two bone-quality states (normal vs. osteoporotic), and two degeneration grades (mild vs. severe) were configured, resulting in 24 pathological combinations. Axial compressive loads corresponding to each BMI level (457 N, 523 N, 588 N, 653 N) were applied, along with ±10 N·m pure moments. Outcome measures—segmental range of motion (ROM), intradiscal pressure (IDP), and facet-joint von Mises stress—were extracted and validated against published benchmarks to confirm model fidelity.Results1. Single-factor effects. With increasing BMI, intradiscal pressure (IDP) at L4–L5 rose by ∼9–12% in non-degenerated discs and loading shifted posteriorly; in degenerated discs, IDP remained lower overall, whereas annular (disc-internal) stress and facet-joint von Mises stress increased. Severe osteoporosis increased vertebral axial-compressive displacement by ∼55% and peak facet-joint stress by ∼48%, indicating reduced structural stiffness and uneven load distribution. Progressive disc degeneration at the index level reduced IDP, most in axial rotation (∼70%), followed by flexion (∼65%) and lateral bending (∼63%), with extension showing the smallest decrease (∼12%); 2. Synergistic effects. Under high BMI (32.65 kg/m2) combined with severe osteoporosis and severe degeneration, posterior-element loading increased non-additively: facet-joint von Mises stress rose from 1.02 to 2.47 MPa, exceeding the sum of single-factor effects. Across 24 condition combinations, cranio-caudal load concentration was evident, with disc-internal (annular) stress peaking in the lower lumbar segments (≈1.90 MPa) under high BMI, osteoporosis, and severe degeneration; 3.“Pseudo-stability” window. When severe degeneration coexisted with osteoporosis, axial-rotation ROM at L4–L5 decreased by ∼18% (mechanical locking), yet internal stresses remained high (facet-joint/endplate stresses up to ≈2.5 MPa), indicating that preserved or even reduced gross motion can mask substantial internal overload.ConclusionThis finite-element study demonstrated that the coexistence of disc degeneration, osteoporosis, and elevated body mass index markedly increases posterior-element loading and disc-internal stresses after unilateral biportal endoscopic decompression. Changes in range of motion were modest overall and tended to decrease when degeneration was combined with osteoporosis, creating a pseudo-stability state in which elevated internal stress is not reflected by gross segmental motion. These findings highlight the importance of considering body weight, bone quality, and disc health together when evaluating postoperative spinal stability and suggest that stress-based assessments may provide a more reliable indicator of hidden instability risk than motion measurements alone.